외과 전공의 수련제도에 대한 설문조사 - 유문원(Moon-Won Yoo); 이인규(In Kyu Lee); 안혜성(Hye Seong Ahn); 김종원(Jong Won Kim); 이혁준(Hyuk-Joon Lee); 이건욱(Kuhn Uk Lee); 양한광(Han-Kwang Yang) (Annals of surgical treatment and research, 2008)
Purpose: This study was aimed to evaluate the current status and problems of surgical residency training program in Korea and to compare 'ward system'(WS) with 'team system'(TS). In WS, residents assigned to a ward take care of the patients in their ward regardless of diseases or specific staffs. In TS, residents assigned to a team or a specific staff treat the patients with specific diseases. Methods: A questionnaire on residency training program was sent to 637 surgical residents working in 69 surgical training hospitals in September 2005. Twenty questions about education, patients' care, and training system were included in the questionnaire and analyzed according to the training systems. Results: The response rate was 18%(113/637). Nineteen residents work in WS, 83 in TS and 11 in other system. Mean education time per week and mean operative time per weekday were longer in WS. The continuity of patients' care was better in TS. The responders chose their own training system as the better one. Conclusion: WS residents considered the advantages of WS as comprehensive training and residents' autonomy and TS residents regarded that of TS as consistent, specialized and intensive training for specific diseases. The results of this study can be used to improve and develop residency training program in surgery. (J Korean Surg Soc 2008;74:1-9) KCI Citation Count: 5